Mancais de deslizamento: estudo de caso - Souza, Tiago Alberto de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The journal bearings used associated with some other mechanical components is extensive, given their relative easy assembly and physical principles involved. This monograph introduces a case of efficiency of a set of bearings, already used, with good market acceptance. The component, now studied, is designed for work on a positive motion pump, model KD825-Uraca, where it is exposed to mechanical loads and continuous lubrication of fluids. Starting from these points of analysis, lubrication and mechanical loads, this work focuses on reviewing parts of the theoretical contents involved presented throughout the course. The purpose of the study is to suggest project improvements or to simply ratify the current project. Necessary data were taken from the technical manuals and in the eventual absence of information, physical measurements were taken of the machine. With computational aid, the sizing and design calculations were revised. It was proposed to use two different commercial lubricants with distinct viscosity values immediately lower and higher one. Based on the results obtained it can be assured that the base lubricant in operation is satisfactory and there are also substitution alternatives, although with some recommmendations

A aplicação de mancais de deslizamento associados a outros componentes mecânicos é vasta, dada sua relativa facilidade de montagem e princípios físicos envolvidos. A presente monografia introduz um estudo de caso da eficiência de um conjunto de mancais, já em uso, com boa aceitação no mercado. O componente, ora estudado, foi projetado para trabalho em uma bomba de deslocamento positivo, modelo KD825-Uraca, onde está exposto a esforços mecânicos e banho contínuo de fluído lubrificante. Partindo destes pontos de análise, lubrificação e esforços mecânicos, este trabalho tem como enfoque revisar parte do conteúdo teórico envolvido apresentado durante todo o curso. O estudo tem ainda por finalidade sugerir melhorias de projeto ou ainda simplesmente ratificar o atual projeto. Dados necessários foram colhidos dos manuais técnicos e na eventual ausência de informações, mensurados na própria máquina. Com auxílio computacional foram revistos os cálculos de dimensionamento e de projeto, propôs-se a utilização de dois diferentes lubrificantes comerciais com um valor de viscosidade imediatamente menor e outro maior. Com base nos resultados colhidos pôde-se observar que lubrificante em operação é satisfatório e há alternativas de substituição salvo algumas recomendações
Sliding Bearings: case study
Keywords: Mancais Mancais; Lubrificação e lubrificantes; Oleos lubrificantes; Lubrification